Impact of sales promotion on consumer buying behavior in the apparel industry - Manish Mishra; Rohit Kushwaha; Nimit Gupta (Cogent Business & Management, 2024)
Sales promotion is a common marketing approach used in the clothing industry to attract customers and increase sales, resulting in the effect of sales promotions on consumer purchasing behavior. Discounts, coupons, flash sales, and loyalty bonuses are all forms of sales promotions. Advertising and marketing of a product increase its reach to more people. The present study looks at how sales promotions influence customer purchasing behavior in the apparel business. The study investigates several sales promotion tactics to attract consumers that can influence consumer decisions in the apparel business. The methodology of the paper is based on a statistical analysis of close-ended questionnaire responses from 330 people aged 18–35 residing in India, as part of field research. The current study asked respondents questions on a 5-point Likert scale. The replies were evaluated using statistical tools from Microsoft, such as Excel, and IBM's Statistical Package for Social Science, as well as statistical techniques such as Regression and Pearson Correlation. According to the study's findings, sales promotions have a positive influence on customer purchase decisions in India's apparel industry. Discounts and coupons add up to savings and have a favorable impact on customer purchasing patterns.This study examines how sales promotions like discounts and coupons influence consumer buying behavior in India's apparel industry. It underscores the significant impact of these strategies on purchasing decisions among young adults, highlighting their importance for attracting customers and driving sales in a competitive market.
Keywords: 650; Apparel; sale; demand; apparel industry; fashion; sales promotion; consumer buying behavior